Weaknesses and strengths of the communicative approach applied in advanced english levels at the foreign Language Department of the University of El Salvador - Arteaga Salguero, Patricia Cecilia; Guevara Rivera, Ana Ruth (2024)
While English is not the most widely spoken language in the world, it is the most widely used by non-native speakers, making the teaching of English as a second foreign language a very important endeavor. The purpose on this essay is to give an overview of the method (in this case Communicative Approach used with Advanced students of the University of El Salvador). This argumentative essay starts by presenting a brief description of language teaching methods used from the beginnings of the teaching language fields to the present. Since the communicative approach is currently being used at the Foreign Language Department at the University of El Salvador, it became the subject of analysis in this paper. Principles and techniques are examined from a practical viewpoint because first hand information from class observation and interviews with experienced teachers from the Department of Foreign Languages at the University of El Salvador was collected. Finally, some drawbacks of the Communicative approach are discussed, and some conclusions are stated.